Law Enforcement Domestic Offender Violenc: Domestic Violence - Mutolib, Undang Abdul; Abdillah, Nanun; Irfan, Asep (Lembaga Yasin AlSys, 2023)
Domestic violence according to Law Number 23 of 2004 is any act against a person, especially women, which results in physical, sexual, psychological, and/or domestic misery or suffering including threats to commit unlawful acts, coercion, or deprivation of independence within the scope of the household. This paper aims to find out how to enforce domestic violence or domestic violence laws. The method used is a descriptive method of analysis, which is to explore information that is in accordance with events in the field through the person concerned or respondent. while the approach used in this study is a qualitative approach. The results of this study show that the Law on Domestic Violence enforced through Law No. 20 of 2003 until now has not been fully enforced effectively to provide protection to victims of domestic violence. Various sociological factors that cause the ineffectiveness of law enforcement include the absence of a common paradigm among law enforcement officials regarding the protection of victims of domestic violence, uneven socialization of legal provisions, unbalanced legal facilities available with cases that occur, not optimal public legal awareness and friction between the values adopted by this law and the values that apply in some communities.